El derecho a la salud desde los principios constitucionales de calidad, eficacia y eficiencia; y su ineficiencia en la Red de Salud Pública - Mena Montero, Aida Yessenia (2023)
The objective of this study has been to analyze the right to health from the constitutional principles of quality, effectiveness and efficiency; and its inefficiency in the public Health Network. For this reason, the following methodological route has been applied: Quantitative, descriptive research, whose sample was made up of 100 users of the public Health Network to whom a survey was applied through a questionnaire made up of 15 linked items divided into the dimensions of quality, effectiveness and efficiency. The most relevant results obtained in this research indicate that 48% of those surveyed state that the level of satisfaction is low with respect to the institution's ability to resolve, improve or facilitate the requirements and activities that condition the provision of the service. 28% of those surveyed state that the level of satisfaction is very low with respect to instruments, technical resources and procedures developed to provide services. 51% of those surveyed state that the level of satisfaction is low regarding the degree of reliability in the services. 48% of those surveyed state that the level of satisfaction is low regarding satisfaction with the performance of the service provider. For all this, it has been concluded by pointing out that the non-compliance with the constitutional principles of quality, effectiveness and efficiency of the right to health has been corroborated, which translates into a level of inefficiency in the public Health Network that must be corrected, considering that the The right to health is an interdependent right and the lack of protection of it results in the violation of other rights such as that of life and personal integrity.